The Influence of Transformational Leadership, Work Conflict, and Work Compensation on Employee Performance in Hospitality Companies - Sabrina Wahyu Afifa; Fajar Satria (Golden Ratio of Data in Summary, 2026)
Employee performance has a dominant influence on the process of achieving company goals. It is hoped that various efforts to improve employee performance will enable employees to provide optimal abilities for the benefit of the company. This research aims to analyze the influence of transformational leadership, work conflict, and work compensation on employee performance. Data collection was carried out by distributing questionnaires to 135 employees. The analytical method used in the research is simple linear regression using statistical software. The research results show that transformational leadership does not significantly influence employee performance, work conflict has an effect on employee performance, and work compensation has an effect on employee performance. and simultaneously, the three independent variables influence employee performance.